Use of mechanical thresholds in a model of feline clinical acute pain and their correlation with the Glasgow Feline Composite Measure Pain Scale scores. Issue 6 (June 2022) - Nicholls, Daniel; Merchant-Walsh, Molly; Dunne, Jerry; Cortellini, Natalia Parrilla; Adami, Chiara
Objectives: The aim of this study was to evaluate the use of mechanical thresholds (MT), measured with the SMALGO (Small Animal ALGOmeter), and to determine whether there was a correlation between MT and Glasgow Feline Composite Measure Pain Scale (CMPS–Feline) scores in cats undergoing ovariohysterectomy. Methods: Client-owned cats undergoing flank ovariohysterectomy were recruited. Pain scores for the pre- and postoperative periods were obtained using the CMPS-Feline in each cat by two independent investigators (A and B). Following CMPS–Feline scoring, MT were measured with the SMALGO, in the surgical area, pre- and postoperatively, only by investigator A. Each cat served as its own control for the comparison of pre- and postoperative variables. Reliability statistics were used to assess the level of inter-observer agreement (A vs B) with respect to pre- and postoperative CMPS–Feline scores, while Spearman's correlation statistics were used to analyse the relationship between MT and CMPS–Feline scores. Results: Twenty-nine cats completed the study. Preoperative MT (340 g [range 108–691]) were significantly higher than postoperatively (233 g [range 19–549]; P = 0.001). CMPS–Feline scores were not found to differ significantly between the preoperative period (2 [range 0–7] for investigator A and 3.2 ± 2.3 for investigator B) and postoperative period (2 [range 0–10] for investigator A and 3 [range 0–8] for investigator B) for either investigator. Reliability statistics revealed that the level of inter-observer agreement with respect to CMPS–Feline was fair for the preoperative assessments but poor for the postoperative evaluations. There was no correlation between MT and CMPS-Feline scores. Conclusions and relevance: Although there was no correlation with CMPS–Feline scores performed at the same timepoint, MT increased postoperatively vs baseline. Assuming that, despite analgesia, susceptibility of the surgical area to mechanical stimulation would increase after surgery, this finding suggests that MT might be useful to assess feline surgical pain. The poor level of inter-observer agreement with respect to postoperative CMPS–Feline scores highlights the potential limitations of this scale.